Selected Papers from the 14th Estuarine and Coastal Modeling Conference (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The 14th Estuarine and Coastal Modeling Conference provided a venue for commercial, academic, and government scientists and engineers from around the world to present and discuss the latest results and techniques in applied estuarine and coastal modeling. Prospective authors were invited to submit papers on a wide range of topic areas, including: Coastal Resiliency Pollutant Transport and Water Quality Prediction Modeling Techniques and Sensitivity Studies Model Assessment Modeling Specific Estuarine and Coastal Systems Model Output Visualization and Analysis Techniques Wave and Sediment Transport Modeling Modeling of Chemicals and Floatables Oil Spill Transport and Fate Modeling Inverse Methods Facility Siting and CSO Studies Data Assimilation Techniques Nowcast/Forecast Modeling Systems Coupled Models of Terrestrial, Atmospheric, Coastal Systems Modeling Systems with Strong Buoyancy Forcing Risk Analysis This Special Issue presents a selection of papers from the conference; the papers give insight, both into current research and commercial developments, and highlight areas where further research or engineering studies are required.